Immune imbalance in Lupus Nephritis: The intersection of T-Cell and ferroptosis - Fan, Yunhe; Ma, Kuai; Lin, Yumeng; Ren, Junyi; Peng, Haoyu; Yuan, Lan; Nasser, Moussa Ide; Jiang, Xuan; Wang, Ke (Frontiers in Immunology, 2024)
Ferroptosis is a novel form of cell death characterized by unlimited accumulation of iron-dependent lipid peroxides. It is often accompanied by disease, and the relationship between ferroptosis of immune cells and immune regulation has been attracting increasing attention. Initially, it was found in cancer research that the inhibition of regulatory T cell (Treg) ferroptosis and the promotion of CD8+ T cell ferroptosis jointly promoted the formation of an immune-tolerant environment in tumors. T-cell ferroptosis has subsequently been found to have immunoregulatory effects in other diseases. As an autoimmune disease characterized by immune imbalance, T-cell ferroptosis has attracted attention for its potential in regulating immune balance in lupus nephritis. This article reviews the metabolic processes within different T-cell subsets in lupus nephritis (LN), including T follicular helper (TFH) cells, T helper (Th)17 cells, Th1 cells, Th2 cells, and Treg cells, and reveals that these cellular metabolisms not only facilitate the formation of a T-cell immune imbalance but are also closely associated with the occurrence of ferroptosis. Consequently, we hypothesize that targeting the metabolic pathways of ferroptosis could become a novel research direction for effectively treating the immune imbalance in lupus nephritis by altering T-cell differentiation and the incidence of ferroptosis.